A (des)construção da noção de gênero nos contos de Katherine Mansfield - Gonçalves, Letícia de Souza [UNESP] (2014)
This study analyzes of the short stories from the collection Bliss & other stories (1920), by the New Zealand author Katherine Mansfield (1888 - 1923), proposing the verification of the deconstruction of gender roles and of the historically categorized discourses in the narratives, and considering the constitution of male and female characters and their relationships. Therefore, we address the relationship between characters of both sexes, the different points of view, the symbols, and, from these concepts, we observe that the categorization of gender and sex is a result of social developments. In pondering the representation of gender in Mansfield's narratives, we expand the matter to social instances, since literature is the representation of the perspective on reality. We use, as a theoretical basis, Virginia Woolf's feminist criticism, Judith Butler's gender performativity and the concept of exotopy by Mikhail Bakhtin, in order to assess the cultural aspects of the gender issue, the literary tradition of women's writing, the ideological identifications and the creation of fictional characters